2013
DOI: 10.1371/journal.pone.0056066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pleistocene Climatic Oscillations on the Phylogeography and Demography of Red Knobby Newt (Tylototriton shanjing) from Southwestern China

Abstract: Factors that determine the genetic structure of species in southwestern China remain largely unknown. In this study, phylogeography and demography of Tylototriton shanjing was investigated from a mitochondrial perspective to address the role of the Quaternary ice ages in shaping phylogeographic history and genetic diversity of Yunnan. A total of 146 individuals from 19 populations across the entire range of the species were collected. We detected four maternal phylogenetic lineages corresponding to four popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 55 publications
1
23
0
3
Order By: Relevance
“…In agreement with Hofmann (), our analysis revealed that the most recent common ancestor of the two main lineages of T. baileyi was dated roughly to the mid‐Pleistocene (0.316 Ma), coinciding with the beginning of the Guxiang (penultimate) glaciation. This estimate overlaps those of Phrynocephalus erythrurus from the southern Chang Thang area (Jin & Liu, ) and of several vertebrate species from the eastern plateau margins (Zhao et al ., ; Fan et al ., ; Yu et al ., ). The most extensive advance of the Guxiang glaciation, c .…”
Section: Discussionmentioning
confidence: 97%
“…In agreement with Hofmann (), our analysis revealed that the most recent common ancestor of the two main lineages of T. baileyi was dated roughly to the mid‐Pleistocene (0.316 Ma), coinciding with the beginning of the Guxiang (penultimate) glaciation. This estimate overlaps those of Phrynocephalus erythrurus from the southern Chang Thang area (Jin & Liu, ) and of several vertebrate species from the eastern plateau margins (Zhao et al ., ; Fan et al ., ; Yu et al ., ). The most extensive advance of the Guxiang glaciation, c .…”
Section: Discussionmentioning
confidence: 97%
“…In these species, the population expansion events often occurred after the LGM (0.022–0.018 Ma BP). In the Yangtze River basin, many native species had experienced strong expansion, such as the red knobby newt Tylototriton shanjing (Yu et al, 2013), the Yunnan spiny frog Nanorana yunnanensis (Zhang et al, 2010) and the grey-cheeked fulvetta Alcippe morrisonia (Song et al, 2009). However, these expansion events all happened much earlier than the LGM.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, based on the demographic stability coupled with low vagility, inference could be made that lineages have sufficient geographical stability to preserve the phylogenetic characteristics of ancient hydrological rearrangement and the geographical background of lineage splitting (Kozak et al, ). Much effort has been made to explore the pattern and extent of Pleistocene climatic oscillations on the geographical distribution and genetic diversity of organisms on the QTP and adjacent areas (Qiu, Fu, & Comes, ; Wan et al, ; Yan et al, ; Yang, Dong, & Lei, ; Yu et al, ; Yuan et al, ). Although complex topography is characterized by buffering effects of dramatic climatic oscillations (Muellner‐Riehl, ; Tzedakis, Lawson, Frogley, Hewitt, & Preece, ), responses to Pleistocene climatic changes vary among species in southwest China.…”
Section: Discussionmentioning
confidence: 99%
“…Population demographic dynamics vary with life history and geography (Hewitt, 2004 (Kozak et al, 2006). Much effort has been made to explore the pattern and extent of Pleistocene climatic oscillations on the geographical distribution and genetic diversity of organisms on the QTP and adjacent areas (Qiu, Fu, & Comes, 2011;Wan et al, 2018;Yan et al, 2013;Yang, Dong, & Lei, 2009;Yu et al, 2013;Yuan et al, 2016).…”
Section: Persistence During Pleistocene Climatic Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation